Hiv, plastic surgery and Brazil: A narrative review - Secanho, Murilo Sgarbi [UNESP]; Neto, Balduino Ferreira De Menezes [UNESP]; Carvalho, Laisa Brandão [UNESP]; De-Oliveira, Ana Beatriz Pedroso Maciel [UNESP]; Chequim, Merimar Maria [UNESP]; Silva, Isabella Dalsico [UNESP]; Palhares, Aristides Augusto [UNESP] (Thieme, 2021)
Introduction: Brazil presents one of the best HIVprograms globally, and one of the characteristics of this approach is multidisciplinarity, where plastic surgery is involved. Objective: To conduct a non-systematic review of what has already been published on HIV by Brazilian plastic surgeons, analyzing the main themes studied. Methods: Research at PubMed, EMBASE, MEDLINE, LILACS, SciELO, Revista Brasileira de Cirurgia Plástica with the following terms: “plastic surgery HIV”, “plastic surgery AIDS”, “HIV plastic surgery”, “AIDS plastic surgery”, “HIV” and “AIDS. Results: We found 862 articles, and after selecting those written by Brazilian plastic surgeons, we reached a final number of 15, produced by 10 institutions from 5 Brazilian states. The most addressed theme was lipodystrophy in 13 publications. Discussion: From the selected articles, it is clear the concentration in the Southeast region. The most addressed theme was lipodystrophy, and the articles on it were published after ordinance GM/MS 2582. Areas such as skin cancer, genetics and surgery for gender reassignment have not been published, although there is already content related to HIV and plastic surgery in other countries. Conclusion: Despite quality publications, there are still areas in which Brazilian plastic surgery research needs to explore concerning HIV/AIDS.
Hiv, cirurgia plástica e Brasil-uma revisão narrativa
Keywords: Ethics; HIV; HIV-associated lipodystrophy syndrome; Plastic surgery; Review, review